Research Trends on Digital Literacy in Quality Education: Bibliometric Analysis Form 2000 to 2024 - Hilhamsyah; Deden Ramdani; Edeh Dike Mariske; Winarno; Suparman; Ika Mariyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Digital Literacy Although many researchers discuss digital literacy, the contribution of digital literacy research to the quality of education is often fragmented, with diverse and unsystematic topics, approaches, and geographical areas. Therefore, this study aims to analyze global research patterns, trends, and focuses over time, thereby providing a foundation for more effective educational development policies and practices. The research method uses bibliometric analysis. The database used is Dimension.ai with the keywords